Analogies Developed by Prospective Classroom Teachers in Science and Technology Training - KARAMUSTAFAOGLU, S. (Asian Journal of Chemistry, 2010)
This study attempts to present the analogies developed by prospective classroom teachers in science and technology training and to bring out their abilities of displaying the relationship between the target and the source. This study is carried out by case study approach with the prospective teachers in 2008-09 education term. They are asked to develop analogies in science and technological subjects after given literature and technological information about analogies. It is determined that the analogies analyzed according to some criteria have been well-developed correctly relating to make the relationship clear between the compared concepts and the concepts to be given. The findings of semi-structured interview made with 10 prospective teachers support that as well. However, in some findings, some analogies that may lead to conceptual misunderstandings and cases where technique of analogy and technique of the experiment are confused are found as well.